2023
DOI: 10.1136/bmj-2022-071620
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and clinical dementia: systematic review and meta-analysis

Abstract: ObjectiveTo investigate the role of air pollutants in risk of dementia, considering differences by study factors that could influence findings.DesignSystematic review and meta-analysis.Data sourcesEMBASE, PubMed, Web of Science, Psycinfo, and OVID Medline from database inception through July 2022.Eligibility criteria for selecting studiesStudies that included adults (≥18 years), a longitudinal follow-up, considered US Environmental Protection Agency criteria air pollutants and proxies of traffic pollution, ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 100 publications
6
32
1
Order By: Relevance
“…Overall, our findings agree with the accumulated evidence on the association between total PM 2.5 and incident dementia . When results were scaled to 1 μg/m 3 , we observed a 2% increased rate of dementia for total PM 2.5 , which is consistent with the overall HR of dementia reported by a recently published meta-analysis among 51 studies identified from 2080 records . Our results are also comparable with 2 other studies of national cohorts in the US, including 1 of more than 12 million US Medicare beneficiaries (aged ≥65 years) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our findings agree with the accumulated evidence on the association between total PM 2.5 and incident dementia . When results were scaled to 1 μg/m 3 , we observed a 2% increased rate of dementia for total PM 2.5 , which is consistent with the overall HR of dementia reported by a recently published meta-analysis among 51 studies identified from 2080 records . Our results are also comparable with 2 other studies of national cohorts in the US, including 1 of more than 12 million US Medicare beneficiaries (aged ≥65 years) .…”
Section: Discussionsupporting
confidence: 92%
“…[34][35][36] When results were scaled to 1 μg/m 3 , we observed a 2% increased rate of dementia for total PM 2.5 , which is consistent with the overall HR of dementia reported by a recently published meta-analysis among 51 studies identified from 2080 records. 37 Our results are also comparable with 2 other studies of national cohorts in the US, 34,36 including 1 of more than 12 million US Medicare beneficiaries (aged ≥65 years). 36 This finding is particularly notable given that our individual-level exposure estimates and standardized dementia classifications should have less measurement error than the zip code-level exposure estimates and administrative outcomes used in the Medicare beneficiaries study.…”
Section: Discussionsupporting
confidence: 83%
“…23 There is emerging evidence of air pollution in cognitive function and dementia. 25 Brain imaging and animal studies could help to further elucidate relevant mechanisms. A recent systematic review suggests that depression, suicide and neurodevelopmental disorders (such as autism for pregnancy-related exposures) may be more common among those exposed to air pollution.…”
Section: The Health Burden Of Air Pollutionmentioning
confidence: 99%
“…The plausible effect of ambient air pollutants on brain pathology, via cerebrovascular disease or inflammation,3 has contributed to an increasing volume of research exploring whether air pollution is a risk factor for dementia. In a linked BMJ paper,4 Wilker and colleagues (doi:10.1136/bmj-2022-071620) examined the association between ambient air pollution and risk of all-cause dementia in a systematic review of 51 longitudinal studies from North America, Europe, Asia, and Australia. They found that higher environmental exposure to fine particulate pollution—particulate matter of less than 2.5 microns in diameter (PM 2.5 )—was associated with an increased risk of dementia: for every 2 µg/m 3 increase in average annual PM 2.5 concentration, overall risk of dementia rose by 4% (hazard ratio 1.04 (95% confidence interval 0.99 to 1.09)).…”
mentioning
confidence: 99%